A protestáns diák mint ideális utazó a 17. század eleji latin nyelvű alkalmi szövegekben - Móré, Tünde (Studia Litteraria, 2026)
During the 16th century, the University of Wittenberg was regarded as the most popular institution among students from the Hungarian Kingdom. They established a student association that published quite extensively, primarily focusing on occasional poetry. Their predominant genre was the valedictory poem, which flourished from 1587 until 1589. The student organization steadily diminished at the end of the 16th century and later was diminished in 1613 due to ecclesiastical laws. The paper analyses two valedictory prints from this late period to explore the narrative regarding the ideal Protestant traveller in the poems.